Composite solid electrolyte membrane and preparation method thereof, all-solid-state lithium battery

By combining the first halide solid electrolyte with the second halide solid electrolyte, and hot pressing treatment, the problem of insufficient ion conductivity of the existing halide solid electrolyte is solved, and the performance of all-solid lithium batteries is improved.

CN119009085BActive Publication Date: 2025-02-28QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411474021.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-28
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing halide solid electrolytes have insufficient ionic conductivity and cannot meet the demand for high transmission rates of lithium-ion batteries.

Method used

By combining the first halide solid electrolyte (LiaMbClxBr6-x) and the second halide solid electrolyte (LieNfCl6-2yYy), a composite solid electrolyte membrane was prepared, and its ionic conductivity was improved by hot pressing treatment.

Benefits of technology

The ionic conductivity of the composite solid electrolyte membrane has been significantly improved, exceeding the conductivity of the raw material halide solid electrolyte, and improving the performance of all-solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119009085B_ABST
    Figure CN119009085B_ABST
Patent Text Reader

Abstract

This application relates to a composite solid electrolyte membrane, a preparation method thereof, and an all-solid-state lithium battery. The composite solid electrolyte membrane includes a first halide solid electrolyte and a second halide solid electrolyte; the first halide solid electrolyte includes Li a M b Cl x Br 6‑x , where 0 < x < 6, 1 < a ≤ 5, a + 3b = 6, and M includes trivalent metal ions; the second halide solid electrolyte includes Li e N f Cl 6‑2y Y y , where 0 < y < 3, e + nf = 6, N includes at least two metal ions, n is the valence of the N ion, n is 2, 3, 4, or 5, and Y is selected from at least one of 2‑ O 2‑ and S; the difference D between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte satisfies: |D| ≤ 1.4 mS / cm. The composite solid electrolyte membrane provided by this application significantly improves the ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite solid electrolyte membrane, a preparation method thereof, and a all-solid-state lithium battery. Background Art

[0002] In recent years, due to the increasing requirements for the safety performance of lithium-ion batteries, solid electrolytes are now often selected to replace liquid electrolytes. One of the major problems with replacing the electrolyte with a solid electrolyte is that the ionic conductivity of the solid electrolyte is lower than the lithium-ion transport rate of the electrolyte.

[0003] Currently, solid electrolytes include polymer electrolytes, oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes, etc. Among them, halide solid electrolytes have received extensive attention due to their high room-temperature ionic conductivity. However, with the increasing requirements for battery performance, higher requirements have also been put forward for the ionic conductivity of halide solid electrolytes.

[0004] In traditional technologies, in order to improve certain properties of halide solid electrolytes, two halide solid electrolytes can be compounded. Although the properties of the obtained composite solid electrolyte are improved in some aspects, the ionic conductivity of the composite halide solid electrolyte is generally between the two and cannot achieve better optimization. Summary of the Invention

[0005] Based on this, it is necessary to provide a composite solid electrolyte membrane, a preparation method thereof, and a all-solid-state lithium battery. The composite solid electrolyte membrane has a higher ionic conductivity compared to the raw material halide solid electrolyte.

[0006] In the first aspect of the present application, a composite solid electrolyte membrane is provided. The composite solid electrolyte membrane includes a first halide solid electrolyte and a second halide solid electrolyte; the first halide solid electrolyte includes Li a M b Cl x Br 6-x , where 0 < x < 6, 1 < a ≤ 5, a + 3b = 6, and M includes trivalent metal ions; the second halide solid electrolyte includes Li e N f Cl 6-2y Y y , where 0 < y < 3, e + nf = 6, N includes at least two metal ions, n is the valence of the N ion, n is 2, 3, 4, or 5, and Y is selected from at least one of O 2- and S 2- ; the difference D between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte satisfies: |D| ≤ 1.4 mS / cm.

[0007] In some embodiments, the ionic conductivity of the composite solid electrolyte membrane is λ0, the ionic conductivity of the first halide solid electrolyte is λ1, and the ionic conductivity of the second halide solid electrolyte is λ2, then λ0, λ1, and λ2 satisfy: λ0>λ1, and λ0>λ2.

[0008] In some embodiments, M is selected from In 3+ , Y 3+ Sc 3+ , Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3+ One or more of .

[0009] In some embodiments, x satisfies: 2≤x≤5.

[0010] In some embodiments, N includes a first metal ion and a second metal ion, wherein n of the first metal ion is 4 and n of the second metal ion is 2, 3 or 5.

[0011] In some embodiments, the first metal ion is selected from Zr 4+ 、Ti 4+ ,Ge 4+ Sn 4+ 、Te 4+ , Pt 4+ and Hf 4+ One or more of .

[0012] In some embodiments, when n of the second metal ion is 2, the second metal ion is selected from Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Cu 2+ , Ra 2+ 、Zn2+ 、Cd 2+ , Hg 2+ Cr 2+ , Mn 2+ 、Co 2+ 、Ni 2+ and Sn 2+ One or more of .

[0013] In some embodiments, when n of the second metal ion is 3, the second metal ion is selected from In 3+ , Y 3+ Sc 3+ , Fe 3 + 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3 + 、Tm 3+ , Yb 3+ He Lu 3+ One or more of .

[0014] In some embodiments, when n of the second metal ion is 5, the second metal ion is selected from Nb 5+ 、As 5+ , Sb 5+ and Bi 5+ One or more of .

[0015] In some embodiments, the mass ratio of the first halide solid electrolyte to the second halide solid electrolyte is (20:80) to (95:5).

[0016] In some embodiments, the composite solid electrolyte membrane has a thickness of 10 μm to 100 μm.

[0017] In some embodiments, the porosity of the composite solid electrolyte membrane is 1% to 10%.

[0018] In some embodiments, the composite solid electrolyte membrane has an ionic conductivity >1.9 mS / cm.

[0019] The second aspect of the present application provides a method for preparing the composite solid electrolyte membrane provided in the first aspect above, and the preparation method comprises the following steps: mixing a first halide solid electrolyte and a second halide solid electrolyte to obtain a mixture; pressing the mixture into a film and then heat treating it, or hot pressing the mixture to obtain a composite solid electrolyte membrane.

[0020] In some embodiments, the temperature of the hot pressing treatment is 80°C to 200°C.

[0021] In some embodiments, the heat pressing treatment time is 0.5 min to 30 min.

[0022] In some embodiments, the pressure of the hot pressing treatment is 10 MPa to 500 MPa.

[0023] The third aspect of the present application provides an all-solid-state lithium battery, which comprises the composite solid-state electrolyte membrane provided by the first aspect and the composite solid-state electrolyte membrane prepared by the preparation method provided by the second aspect.

[0024] Compared with the traditional technology, this application has at least the following beneficial effects:

[0025] The composite solid electrolyte membrane provided in the present application has a higher ionic conductivity than the raw material halide solid electrolyte by synergizing the first halide solid electrolyte and the second halide solid electrolyte, and controlling the difference between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte to within 1.4 mS / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of a method for preparing a composite solid electrolyte membrane in an embodiment provided in the present application.

[0027] Figure 2 Li3Y 0.5 Dy 0.5 DSC curve of Cl3Br3 material. DETAILED DESCRIPTION

[0028] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0029] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] Unless otherwise specified, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or present) and B is false (or absent); A is false (or absent) while B is true (or present); or both A and B are true (or present).

[0037] A first aspect of the present application provides a composite solid electrolyte membrane, which includes a first halide solid electrolyte and a second halide solid electrolyte. The first halide solid electrolyte includes Li a M b Cl x Br 6-x , where 0 < x < 6, 1 < a ≤ 5, a + 3b = 6, and M includes trivalent metal ions. The second halide solid electrolyte includes Li e N f Cl 6-2y Y y , where 0 < y < 3, e + nf = 6, N includes at least two metal ions, n is the valence of the N ion, n is 2, 3, 4, or 5, and Y is selected from at least one of O 2- and S 2- ; the difference D between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte satisfies: |D| ≤ 1.4 mS / cm.

[0038] The composite solid electrolyte membrane provided by the present application, through the synergistic cooperation of the first halide solid electrolyte and the second halide solid electrolyte, and controlling the difference between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte within 1.4 mS / cm, so that the composite solid electrolyte membrane has a higher ionic conductivity compared to the raw material halide solid electrolyte.

[0039] It can be understood that controlling the difference between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte within 1.4 mS / cm avoids affecting ion transport between each other and ensures the exertion of the synergistic effect of the first halide solid electrolyte and the second halide solid electrolyte.

[0040] In some of these embodiments, the relationship between the ionic conductivity λ0 of the composite solid electrolyte membrane and the ionic conductivity λ1 of the first halide solid electrolyte and the ionic conductivity λ2 of the second halide solid electrolyte satisfies: λ0 > λ1 and λ0 > λ2.

[0041] In some embodiments, x satisfies: 2≤x≤5, including but not limited to 2, 3, 4, and 5. Within the above x value range, the doping ratio of Cl and Br can be adjusted, further improving the ionic conductivity of the composite solid electrolyte membrane.

[0042] In some embodiments, M is selected from In 3+ , Y 3+ Sc 3+ , Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3+ One or more of .

[0043] In some embodiments, N includes a first metal ion and a second metal ion, n of the first metal ion is 4, and n of the second metal ion is 2, 3 or 5.

[0044] It can be understood that when the first metal ion is tetravalent, the combination with the second metal ion of another valence further improves the ionic conductivity of the composite solid electrolyte membrane.

[0045] In some embodiments, the first metal ion is selected from Zr 4+ 、Ti 4+ ,Ge 4+ Sn 4+ 、Te 4+ , Pt 4+ and Hf 4+ One or more of .

[0046] In some embodiments, when n of the second metal ion is 2, the second metal ion is selected from Be 2+ Mg 2+ , Ca 2 + , Sr 2+ , Ba 2+, Cu 2+ , Ra 2+ 、Zn 2+ 、Cd 2+ , Hg 2+ Cr 2+ , Mn 2+ 、Co 2+ 、Ni 2+ and Sn 2+ One or more of .

[0047] In some embodiments, when n of the second metal ion is 3, the second metal ion is selected from In 3+ , Y 3+ Sc 3 + , Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3 + , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3+ One or more of .

[0048] In some embodiments, when n of the second metal ion is 5, the second metal ion is selected from Nb 5+ 、As 5+ , Sb 5 + and Bi 5+ One or more of .

[0049] In some embodiments, the mass ratio of the first halide solid electrolyte to the second halide solid electrolyte is (20:80) to (95:5), including but not limited to 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, and 95:5.

[0050] Furthermore, the mass ratio of the first halide solid electrolyte to the second halide solid electrolyte is (35:65) to (70:30).

[0051] In some embodiments, the thickness of the composite solid electrolyte membrane is 10 μm to 100 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm. Further, the thickness of the composite solid electrolyte membrane is 10 μm to 50 μm.

[0052] In some embodiments, the porosity of the composite solid electrolyte membrane is 1% to 10%, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Further, the porosity of the composite solid electrolyte membrane is 1% to 5%.

[0053] In some embodiments, the ionic conductivity of the composite solid electrolyte membrane is >1.9 mS / cm, including but not limited to 2 mS / cm, 2.5 mS / cm, 3 mS / cm, 3.5 mS / cm, 4 mS / cm, and 4.5 mS / cm.

[0054] In some embodiments, the composite solid electrolyte membrane is obtained by hot pressing a first halide solid electrolyte and a second halide solid electrolyte, and the hot pressing temperature is 80°C to 200°C.

[0055] The possible reason is that the first halide solid electrolyte has a certain fluidity at a temperature greater than or equal to 80°C, so it can better fill the gap in the second halide solid electrolyte, and during the hot pressing process, the density of the composite solid electrolyte membrane is improved, the porosity is reduced, the resistance at the interface is reduced, and the ion migration rate is increased. The above is only a speculation on the mechanism of the present application and does not constitute a limitation on the scope of protection of the present application.

[0056] The second aspect of the present application provides a method for preparing the composite solid electrolyte membrane provided in the first aspect, such as Figure 1 As shown, the preparation method comprises the following steps:

[0057] S1. Mixing a first halide solid electrolyte and a second halide solid electrolyte to obtain a mixture.

[0058] S2. The mixed material is pressed into a film and then heat treated, or the mixed material is hot pressed to obtain a composite solid electrolyte membrane.

[0059] The preparation method of the composite solid electrolyte membrane provided by the present application ensures the uniform distribution of the first halide solid electrolyte and the second halide solid electrolyte in the composite solid electrolyte membrane through a mixing step, thereby realizing a uniform ion migration channel. The first halide solid electrolyte has a certain fluidity under high temperature environment, so it can better fill the gap in the second halide solid electrolyte. Combined with the pressing step, the compactness of the composite solid electrolyte membrane is improved, the porosity is reduced, the resistance at the interface is reduced, and the ion migration rate is increased.

[0060] In some specific embodiments, in step S2, the mixture is subjected to a hot pressing process to obtain a composite solid electrolyte membrane.

[0061] In some embodiments, the temperature of the hot pressing treatment is 80° C. to 200° C., including but not limited to 80° C., 100° C., 120° C., 140° C., 160° C., 180° C., and 200° C. Within the above temperature range, the first halide solid electrolyte has a certain fluidity while maintaining the stability of its crystal structure, so that the prepared composite solid electrolyte membrane has both excellent ionic conductivity and mechanical stability.

[0062] In some embodiments, the time of hot pressing treatment is 0.5 min to 30 min, including but not limited to 0.5 min, 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min.

[0063] In some embodiments, the pressure of the hot pressing treatment is 10 MPa to 500 MPa, including but not limited to 10 MPa, 50 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, and 500 MPa.

[0064] In some embodiments, the pressure for pressing into film is 100 MPa~300 MPa, including but not limited to 100 MPa, 150 MPa, 200 MPa, 250 MPa, and 300 MPa.

[0065] In some embodiments, the heat treatment temperature is 80°C to 200°C, including but not limited to 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, and 200°C.

[0066] The third aspect of the present application provides an all-solid-state lithium battery, which comprises the composite solid-state electrolyte membrane provided by the first aspect and the composite solid-state electrolyte membrane prepared by the preparation method provided by the second aspect.

[0067] The present application will be further described below with reference to specific embodiments and comparative examples.

[0068] Embodiments 1 to 10

[0069] Preparation of composite solid electrolyte membrane:

[0070] S1. Mixing a first halide solid electrolyte and a second halide solid electrolyte to obtain a mixture.

[0071] S2. The mixture is subjected to hot pressing treatment at 160° C. and 100 MPa for 10 min to obtain a composite solid electrolyte membrane. The thickness of the composite solid electrolyte membrane is 20 μm.

[0072] All-solid-state lithium battery:

[0073] The composite solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, an all-solid-state lithium battery is obtained.

[0074] In the examples prepared according to the above method, specific parameters are shown in Table 1 below.

[0075] Table 1

[0076]

[0077] Comparative Example 1

[0078] Preparation of composite solid electrolyte membrane:

[0079] S1, Li3Y 0.5 Dy 0.5 Cl3Br3 and Li 2.2 Zr 0.9 Ba 0.1 Cl 4.5 O 0.75 The mixture is mixed to obtain a mixed material.

[0080] Among them, Li3Y 0.5 Dy 0.5 The ionic conductivity of Cl3Br3 is 2.72 mS / cm, Li 2.2 Zr 0.9 Ba 0.1 Cl 4.5 O 0.75 The ionic conductivity is 0.76 mS / cm.

[0081] S2. The mixture is subjected to hot pressing treatment at 160° C. and 100 MPa for 10 min to obtain a composite solid electrolyte membrane. The thickness of the composite solid electrolyte membrane is 20 μm.

[0082] All-solid-state lithium battery:

[0083] The composite solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, an all-solid-state lithium battery is obtained.

[0084] Comparative Example 2

[0085] Preparation of composite solid electrolyte membrane:

[0086] S1, Li3Y 0.5 Dy 0.5 Cl3Br3 and Li 2.25 Zr 0.75 Dy 0.25 I 4.5 O 0.75 The mixture is mixed to obtain a mixed material.

[0087] Among them, Li3Y 0.5 Dy 0.5 The ionic conductivity of Cl3Br3 is 2.72 mS / cm, Li 2.25 Zr 0.75 Dy 0.25 I 4.5 O 0.75 The ionic conductivity is 1.57 mS / cm.

[0088] S2. The mixture is subjected to hot pressing treatment at 160° C. and 100 MPa for 10 min to obtain a composite solid electrolyte membrane. The thickness of the composite solid electrolyte membrane is 20 μm.

[0089] All-solid-state lithium battery:

[0090] The composite solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, an all-solid-state lithium battery is obtained.

[0091] Comparative Example 3

[0092] Preparation of solid electrolyte membrane:

[0093] Opposite 2.25 Zr 0.75 Dy 0.25 Cl 4.5 O 0.75 The solid electrolyte membrane was obtained by hot pressing at 160° C. and 100 MPa for 10 minutes. The thickness of the solid electrolyte membrane was 20 μm.

[0094] All-solid-state lithium battery:

[0095] The solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, an all-solid-state lithium battery is obtained.

[0096] Comparative Example 4

[0097] Preparation of solid electrolyte membrane:

[0098] For Li3Y 0.5 Dy 0.5 Cl3Br3 was hot-pressed at 160°C and 100 MPa for 10 min to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0099] All-solid-state lithium battery:

[0100] The solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, an all-solid-state lithium battery is obtained.

[0101] Performance Testing

[0102] (1) Melting point test

[0103] The first halide solid electrolyte Li3Y 0.5 Dy 0.5 The Cl3Br3 material was placed in a crucible and heated from 30°C to 300°C at a rate of 10°C / min under a nitrogen atmosphere to obtain Li3Y 0.5 Dy 0.5 DSC curve of Cl3Br3 material. Figure 2 shown.

[0104] (2) Porosity test

[0105] True density test: The true density of the composite solid electrolyte membrane is obtained by the true density meter. The test process is as follows: After the power is turned on, the instrument is preheated according to the requirements of the instrument manual to ensure that the instrument reaches a stable working state. Put the sample to be tested into the sample pool, press the measurement button, and the instrument will automatically measure the density. After the measurement is completed, the instrument will automatically record the data and calculate the true density value ρ 真 .

[0106] Compacted density test: Add 100 mg of powder into a φ10 mm mold, apply a pressure of 375 MPa and maintain the pressure for 3 minutes, then remove the mold to obtain a compacted sheet, measure its thickness, and calculate its compacted density ρ 压实 .

[0107] Porosity: Porosity is (ρ 真 -ρ 压实) / ρ 真 .

[0108] (3) Ionic conductivity test

[0109] At 25° C., the ionic conductivities of the first halide solid electrolyte, the second halide solid electrolyte, the composite solid electrolyte membrane and the solid electrolyte membrane in the above embodiments and comparative examples were tested. The test results are shown in Table 2.

[0110] (4) Discharge specific capacity test

[0111] The all-solid-state lithium battery in the above embodiment and comparative example was tested for capacity, left to stand for 1 min, discharged at a current of 0.1 C until the cut-off voltage was 2.7 V, and the first discharge capacity was recorded. The results are shown in Table 2 below.

[0112] (5) Cyclic performance test

[0113] The all-solid-state lithium battery in the above embodiment and comparative example was subjected to a cycle test. At a temperature of 25°C ± 2°C, the first step was to charge at 0.1C to a final voltage of 4.5V, a cut-off current of 0.05C, and stand for 30 minutes; the second step was to discharge at 0.1C to a final discharge voltage of 2.7V, record the discharge capacity, and stand for 30 minutes; the first and second steps were cycled to test the cycle performance of the battery for 500 cycles. The results are shown in Table 2 below.

[0114] Table 2

[0115]

[0116] As shown in Table 2, by comparing Examples 1 to 10 with Comparative Examples 1 to 4, it can be seen that the composite solid electrolyte membrane provided in the present application has excellent ionic conductivity, thereby improving the discharge capacity and capacity retention rate of the all-solid-state lithium battery.

[0117] like Figure 2 As shown, an endothermic peak can be observed at 80℃~200℃, at which time the first halide solid electrolyte Li3Y 0.5 Dy 0.5 The Cl3Br3 material melts and produces a certain fluidity, so it can better fill the gaps in the second halide solid electrolyte.

[0118] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane includes a first halide solid electrolyte and a second halide solid electrolyte; The first halide solid electrolyte includes Li a M b Cl x Br 6-x , where 0 < x < 6, 1 < a ≤ 5, a + 3b = 6, and M includes trivalent metal ions; The M is selected from In 3+ , Y 3+ Sc 3+ , Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3+ One or more of; The second halide solid electrolyte includes Li e N f Cl 6-2y Y y , where 0 < y < 3, e + nf = 6, N includes at least two metal ions, n is the valence of the N ion, n is 2, 3, 4 or 5, and Y is selected from at least one of 2- O 2- and S; The difference D between the ionic conductivity of the first halide solid electrolyte and the ionic conductivity of the second halide solid electrolyte satisfies: |D|≤1.4 mS / cm; The ionic conductivity of the composite solid electrolyte membrane is λ0, the ionic conductivity of the first halide solid electrolyte is λ1, and the ionic conductivity of the second halide solid electrolyte is λ2. Then, λ0, λ1, and λ2 satisfy: λ0>λ1, and λ0>λ2.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The x satisfies: 2≤x≤5.

3. The composite solid electrolyte membrane according to claim 1, characterized in that: The N includes a first metal ion and a second metal ion, wherein n of the first metal ion is 4, and n of the second metal ion is 2, 3 or 5.

4. The composite solid electrolyte membrane according to claim 3, characterized in that: The first metal ion is selected from Zr 4+ 、Ti 4+ ,Ge 4+ Sn 4+ 、Te 4+ , Pt 4+ and Hf 4+ One or more of; and / or, When n of the second metal ion is 2, the second metal ion is selected from Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Cu 2+ , Ra 2 + 、Zn 2+ 、Cd 2+ , Hg 2+ Cr 2+ , Mn 2+ 、Co 2+ 、Ni 2+ and Sn 2+ One or more of; and / or, When n of the second metal ion is 3, the second metal ion is selected from In 3+ , Y 3+ Sc 3+ , Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ He Lu 3 + One or more of; and / or, When n of the second metal ion is 5, the second metal ion is selected from Nb 5+ 、As 5+ , Sb 5+ and Bi 5+ One or more of .

5. The composite solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The mass ratio of the first halide solid electrolyte to the second halide solid electrolyte is (20:80) to (95:5).

6. The composite solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The composite solid electrolyte membrane meets at least one of the following characteristics: (1) The thickness of the composite solid electrolyte membrane is 10 μm to 100 μm; (2) The porosity of the composite solid electrolyte membrane is 1%-10%; (3) The ionic conductivity of the composite solid electrolyte membrane at 25° C. is greater than 1.9 mS / cm.

7. A method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing the first halide solid electrolyte and the second halide solid electrolyte to obtain a mixture; The composite solid electrolyte membrane is obtained by pressing the mixed material into a film and then performing heat treatment, or performing heat pressing on the mixed material.

8. The method for preparing a composite solid electrolyte membrane according to claim 7, characterized in that: The temperature of the hot pressing treatment is 80°C to 200°C; and / or, The heat pressing treatment time is 0.5min to 30min; and / or, The pressure of the hot pressing treatment is 10MPa~500MPa.

9. An all-solid-state lithium battery, characterized in that: A composite solid electrolyte membrane comprising the composite solid electrolyte membrane according to any one of claims 1 to 6 or a composite solid electrolyte membrane prepared by the preparation method according to claim 7 or 8.

Citation Information

Patent Citations

  • Solid electrolyte material and cell using same

    CN112930319A

  • Preparation method of composite solid electrolyte membrane and lithium ion battery

    CN117059887A